Does Exposure to Other Ethnic Regions Promote National Integration? : Evidence from Nigeria - Okunogbe, Oyebola (World Bank, Washington, DC, 2018)
This paper examines how temporary exposure to a different ethnic region affects national integration using original survey data from participants in Africa’s largest national youth service program. Seven years later, participants randomly assigned to serve in a state with a different ethnic majority are five times more likely to live all across the country compared to those who served in their ethnic region. They have more interethnic romantic relationships and express greater national pride. Nevertheless, immersion in a different ethnic region strengthens participants’ ethnic pride and favorable attitudes towards co-ethnics. The results suggest that national and ethnic identity can thrive together.